Analysis on stress characteristics of floor in thick seam working face at initial stage of fully mechanized top coal caving mining - Guo, Liquan; Ou, Yuanchao; Liu, Chang (IOP conference series. Earth and environmental science, 2021)
Coal seam working face mining will cause the redistribution of the stress field in the mining floor, which results in the deformation and damage of the coal and rock mass. The stress on the open-off cut floor of the working face at the initial stage of fully mechanized top coal mining of coal seam is different from other positions. Knowing the change of the stress characteristics of the rock formation in this area is significant for the safe mining of the coal seam. To investigate the characteristics of the stress changes in the rock formation in the open-off cut floor of the working face at the initial stage of fully mechanized top coal mining of thick coal seam, a distributed fiber-optic strain testing technology was used for dynamic monitoring of the stress distribution in the rock formation in the open-off cut floor of the working face, based on the working face of a mine in Huainan, China. The results showed that the change in fiber-optic strain distribution throughout the monitoring period corresponded well with the lithology of the formation. The fiber-optic strain in the ⑥ mudstone, ⑦ limestone, and ⑧ fine sandstone in the control area of the drilled fiber optic cable was subject to compressive strain, indicating that the floor of the working face was subject to overall compression due to the influence of the mining action. The fault structure limited the extent and magnitude of the effects of mining stresses laterally in the rock formation. The overall fiber-optic strain in the ④ sandy mudstone and ⑤ fine sandstone located on the outside of the open-off cut floor of the working face did not change significantly. The lagged impact distance of the mining stress was 35 m.